Modelling and analysis of pad surface topography and slurry particle size distribution effects on material removal rate in chemical mechanical planarisation. (6th September 2005) - Wang, Changxue; Sherman, Peter; Chandra, Abhijit
Traditionally, static or steady state models of material removal rate (MRR) in a chemical mechanical planarisation (CMP) process have been developed, and the effects of properties of consumables such as pad or slurry particles on MRR have been investigated. There also exist dynamic or transient models of the CMP process; however, the effect of slurry particle size and distribution is typically neglected in these dynamic models. The present work combines these different approaches by attempting to develop a dynamic model of the CMP process capable of representing MRR decay, which can also account for the effects due to slurry particle size and distribution.